2020
DOI: 10.1158/1078-0432.ccr-19-1359
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Citrate Lyase Epigenetically Potentiates Oxidative Phosphorylation to Promote Melanoma Growth and Adaptive Resistance to MAPK Inhibition

Abstract: Enhanced lipogenesis and mitochondrial function are two critical metabolic characteristics in melanoma. Here, we demonstrate that lipogenic enzyme ACLY epigenetically potentiates mitochondrial oxidative phosphorylation, thus acting as an oncogenic factor to promote melanoma growth and MAPK inhibition adaptive resistance. To be specific, up-regulated ACLY enhances the activity of acetyltransferase P300 and then increases the histone acetylation at MITF locus to activate MITF-PGC1α axis transcription and mitocho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…In addition to participating in lipid metabolism in the cytosol, nucleus-translocated ACLY generates acetyl-CoA for histone acetylation and gene transcription regulation ( Wellen et al, 2009 ). In melanoma cells, ACLY enhances acetyltransferase p300-dependent histone acetylation, thereby promoting PPARγ coactivator (PGC) 1α–mediated mitochondrial biogenesis for cell proliferation ( Guo et al, 2020 ). In PDAC, glioma, and prostate cancer cells, growth factors or oncogenic K-Ras expression promotes AKT–ACLY signaling, histone acetylation, cell proliferation, and tumor growth ( Carrer et al, 2019 ; Lee et al, 2014 ).…”
Section: Lipogenesismentioning
confidence: 99%
“…In addition to participating in lipid metabolism in the cytosol, nucleus-translocated ACLY generates acetyl-CoA for histone acetylation and gene transcription regulation ( Wellen et al, 2009 ). In melanoma cells, ACLY enhances acetyltransferase p300-dependent histone acetylation, thereby promoting PPARγ coactivator (PGC) 1α–mediated mitochondrial biogenesis for cell proliferation ( Guo et al, 2020 ). In PDAC, glioma, and prostate cancer cells, growth factors or oncogenic K-Ras expression promotes AKT–ACLY signaling, histone acetylation, cell proliferation, and tumor growth ( Carrer et al, 2019 ; Lee et al, 2014 ).…”
Section: Lipogenesismentioning
confidence: 99%
“…Therefore, ATP1B4 is not only the source gene of TCONS_00279168 but also its target gene. ATP1B4 is a member of ATPase Na+/K+ transporting family, which is believed to contribute to the activity of the MAPK signaling pathway, which is well supported by the studies in humans [ 53 , 54 ]. Furthermore, ATP1B4 , as an important member of ATPase Na+/K+ transporting beta M family, which is involved in the regulation of gene expression level in TGF-β signaling pathway as exemplified by an increase of expression of inhibitory Smad7.…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, exosomal HSPC111 induced the pre-metastatic niche in liver to promote CRLM. A set of recent studies revealed that the elevation of ACLY expression and activity promotes cancer cell growth and metastasis [42,43] , and phosphorylation of ACLY contributes to cellular acetyl-CoA production and then increases histone acetylation [44] . In our study, we observed exosomal HSPC111 treatment speci cally affected the acetylation of H3K27 in CAFs without affecting acetylation of other histone protein.…”
Section: Discussionmentioning
confidence: 99%